EXTERNAL MALE GENITALIA OF FOUR SPECIES OF GÈNUS ERISTALIS LATREILLE (SYRPHIDAE : DIPTERA) - SINGH, AWTAR; SODHT, NAVJOT S.; GUPTA, VIPUL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
A study of external male genitalia of four species of genus Eristals Latreille sir. E curvipes Schiner, E. arvorum Fabricius, E. quinquelineatus Fabricius and E obscuritarsis de Meijere has been made.